2012
DOI: 10.1080/10286020.2011.647503
|View full text |Cite
|
Sign up to set email alerts
|

A secondary metabolite amberin fromAmberboa ramosa

Abstract: Amberin (1), a new sesquiterpene lactone, has been isolated from the ethyl acetate soluble fraction of Amberboa ramosa together with apigenin (2), jaseocidine (3), crysoeriol (4), and 3β, 8α-dihydroxy-11α-methyl-1αH, 5αH, 6βH, 7αH, 11βH-guai-10(14), 4 (15)-dien-6, 12-olide (5). The structures of the isolated compounds have been elucidated by 1D and 2D NMR spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Literature survey revealed that triterpenoids, flavonoids, steroids and sesquiterpene lactones have previously been reported from this species [4,5]. In this study we have isolated four guaianolides (sesquiterpenes) out of which Amberbin C ( 1 ) was identified as a new compound while other three Amberin ( 2 ) [6], Amberbin A ( 3 ) and Amberbin B ( 4 ) [7] were previously been reported from the same source. All structures were elucidated by using different spectroscopic techniques like UV, IR, EI-MS, 1D and 2D NMR techniques.…”
Section: Introductionmentioning
confidence: 71%
“…Literature survey revealed that triterpenoids, flavonoids, steroids and sesquiterpene lactones have previously been reported from this species [4,5]. In this study we have isolated four guaianolides (sesquiterpenes) out of which Amberbin C ( 1 ) was identified as a new compound while other three Amberin ( 2 ) [6], Amberbin A ( 3 ) and Amberbin B ( 4 ) [7] were previously been reported from the same source. All structures were elucidated by using different spectroscopic techniques like UV, IR, EI-MS, 1D and 2D NMR techniques.…”
Section: Introductionmentioning
confidence: 71%
“…Te phytochemical investigations have confrmed the presence of sesquiterpenes, favonoid (jaceosidine, apigenin, chrysoeriol, 5,7,4′-trihydroxy-3,8-dimethoxylfavone), long-chain esters, cycloartane-triterpenoids, lactone (cynaropicrin, amberen, ramosine), glycoside (Kaempferol 5-O-β-D-gluco-pyranoside), alkaloids, carbohydrates, tannins, saponins, anthraquinones, and steroids in O. ramosa Roxb. extracts [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical investigations revealed the presence of flavone (jaceosidine), sesquiterpene lactone (cynaropicrine, amberin, amberbins A, amberbins B, apigenin, crysoeriol, jaseocidine, ramosine, tricontane), longchain esters, cycloartane-triterpenoids and glycoside (5,7,4'-trihydroxy-3,8-dimethoxylflavone 5-O-β-D-gluco -pyranoside) (Forgacs et al, 1981;Khan et al, 2004;Khan et al, 2005a;Khan et al, 2005b;Ibrahim et al, 2010;Ibrahim et al, 2012).…”
Section: Introductionmentioning
confidence: 99%